2018
DOI: 10.1177/0885328218797545
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of porous hydroxyapatite/β-cyclodextrin-based polyurethane composite scaffolds for bone tissue engineering

Abstract: In this study, novel porous scaffolds containing hydroxyapatite and b-cyclodextrin-based polyurethane were first successfully fabricated by polymerizing b-cyclodextrin with hexamethylene diisocyanate and hydroxyapatite in situ for bone tissue engineering. The physicochemical and mechanical properties as well as cytocompatibility of porous scaffolds were investigated. The results showed that polyurethane reinforced with hydroxyapatite composites had cancellous bone-like porous structure. The mechanical strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…22 Previous studies have shown that the Hydroxyapatite (HA) incorporation in the composition of the scaffold favored osteoconduction, biocompatibility, cell proliferation and differentiation, in addition to being present as the main inorganic structure responsible for the regenerative process. 22,23,24 Although HA has excellent properties, composite materials may have some disadvantages as they make biomaterials highly friable, requiring the addition of other components to improve fracture strength. 25 The graphene particles have been shown to increase the mechanical strength of these bioceramic composites.…”
Section: Introductionmentioning
confidence: 99%
“…22 Previous studies have shown that the Hydroxyapatite (HA) incorporation in the composition of the scaffold favored osteoconduction, biocompatibility, cell proliferation and differentiation, in addition to being present as the main inorganic structure responsible for the regenerative process. 22,23,24 Although HA has excellent properties, composite materials may have some disadvantages as they make biomaterials highly friable, requiring the addition of other components to improve fracture strength. 25 The graphene particles have been shown to increase the mechanical strength of these bioceramic composites.…”
Section: Introductionmentioning
confidence: 99%
“…There was also a peak at 1161 cm −1 belonging to the absorption of C–O–C vibration. 39 According to the FT-IR spectrum for the β-CDs/Ni-based MOF composite, all the peaks corresponding to the β-CDs and Ni-based MOF were still there in the final structure of the β-CDs/Ni-based MOF specimen, strongly confirming the successful fabrication of the polymeric fibrous composite.…”
Section: Resultsmentioning
confidence: 76%
“…In addition, this β-CD composite scaffold has the potential to be applied in bone repair and regeneration. 39 In Lukášek et al ’s report, a cyclodextrin-enriched composite scaffold revealed better performance in in vitro experiments compared with pristine polycaprolactone or polypyrrole-covered polycaprolactone scaffolds. 41 Yi et al indicated that the poly( l -lactide)-β-CD-hydroxyapatite composite possessed a rather large biocompatibility and bioactivity, and it could be a promising candidate as a bone tissue engineering material.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…[32]. β-Cyclodextrin (β-CD), another biobased monomer with a lipophilic cavity and a hydrophilic exterior, has attracted also attention due to its accessibility, lowest cost, environmentally friendly, excellent biocompatibility and ability to form inclusion complexes [33]. This natural product, which is obtained through enzymatic conversion from starch, is extensively used in separation and purification [34,35].…”
Section: Introductionmentioning
confidence: 99%